A Childhood Inflammatory Myopathy with Cytochrome Oxidase Deficiency: Which Came First, the Chicken or the Egg? - Gülden Diniz; Önder Yavaşcan; Ümit Başak Şarkış; Zübeyde Yıldırım; Caner Alparslan; Can Öztürk; Afig Berdeli (Galenos Publishing House, 2023)
Inflammatory myopathies are autoimmune disorders rarely seen in childhood. Normally high-dose corticosteroid is the current treatment for inflammatory myopathies. For a specific subgroup of patients with inflammatory myopathy with cytochrome oxidase (COX)-negative myofibers that do not typically respond to corticosteroid treatment, and methotrexate (MTX) is used for therapy. Herein we present a 10-year-old girl who initially received clinical diagnosis of juvenile inflammatory myopathy which did not respond to corticosteroid treatment. Examination of her muscle biopsy specimen showed the presence of COX-negative muscle fibers which are very rarely seen in childhood inflammatory myopathies, and she was diagnosed as inflammatory myopathy characterized with COX-negative myofibers. The patient, who recovered with MTX therapy underwent genetic examination 3 years after the treatment was terminated. The sequence analyses of mitochondrial DNA (mtDNA) identified 19 variants in the rRNA, ND2, ND4, ND5, COX1, COX3, and CytB genes of the mtDNA of the patient and her mother. These mutations generally induce the production of synonym amino acids. However, four missense mutations on the ND4, ATP6, and CytB genes have caused structural changes in amino acids. None of these mutations have been previously reported as pathogenic variants. We have thought that these variations in such essential genes might destabilize mtDNA and could probably affect the ATP synthesis in our patient. Our final diagnosis was established based on abnormal inflammatory response induced by a hereditary mtDNA defect in a child with mitochondrial myopathy, rather than an inflammatory myopathy with COX deficiency.